The Independent Value of Neutrophil to Lymphocyte Ratio in Gouty Arthritis: A Narrative Review - Chen Y; Liu J; Li Y; Cong C; Hu Y; Zhang X; Han Q (Dove Medical Press, 2023)
Yiming Chen,1,2 Jian Liu,1- 3 Yang Li,1 Chengzhi Cong,1 Yuedi Hu,1 Xianheng Zhang,1 Qi Han1 1Department of Rheumatology, the First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui Province, People's Republic of China; 2Anhui Key Laboratory of Application and Development of Internal medicine of Modern Chinese Medicine, Anhui University of Chinese Medicine, Hefei, Anhui Province, People's Republic of China; 3National Traditional Chinese Medicine Inheritance and Innovation Center, Hefei, Anhui Province, People's Republic of ChinaCorrespondence: Jian Liu, Department of Rheumatology, the First Affiliated Hospital of Anhui University of Chinese Medicine, Hefei, Anhui Province, People's Republic of China, Tel +86 13955109537, Email liujianahzy@126.comAbstract: Since the incidence of gouty arthritis (GA) exhibits yearly increases, accurate assessment and early treatment have significant values for improving disease conditions and monitoring prognosis. Neutrophil to lymphocyte ratio (NLR) is a common indicator in blood routine, which has the characteristics of easy access and low cost. In recent years, NLR has been proven to be an effective indicator for guiding the diagnosis, treatment, and prognosis of various diseases. Moreover, NLR has varying degrees of relationship with various inflammatory biomarkers, which can affect and reflect the inflammatory response in the body. This paper reviews the independent value of NLR for GA and its underlying molecular pathological mechanisms, intending to contribute to the further application of NLR.Keywords: neutrophil to lymphocyte ratio, gouty arthritis, inflammatory response, neutrophils, disease activity